Pakistan’s national COVID-19 response: lessons from an emergent response to the pandemic - Khan, Adnan Ahmad; Abdullah, Mujahid; Khan, Romesa; Kazmi, Twangar; Sultan, Faisal; Aamir, Shirin; Khawaja, Aamir Ashraf; Khan, Ayesha (Frontiers in Public Health, 2024)
Introduction In 2020, Pakistan faced the formidable challenge of the COVID-19 pandemic with an existing yet disjointed healthcare infrastructure, that included by over 18,000 public and an estimated 75,000 private health facilities and some elements of an epidemic surveillance and response system. This descriptive study examines how Pakistan developed a COVID-19 response, driven by establishing a central coordination and decision-making mechanism to overcome these systemic challenges. Methods The study is based on interviews and interactions of the many actors in the response by the authors, who also participated in nearly all proceedings of the National Command and Operation Centre (NCOC) and many of the National Coordination Committee (NCC). This information is supplemented by reviewing documents, reports, news items, media and social media, and journal articles. Results The study highlights the critical role of political arrangement, where the NCC, comprising of ministers, bureaucrats, and military personnel, facilitated federal and provincial integration. The NCC found resources and set policy. Its direction was implemented by the NCOC, a top-down yet inclusive platform, integrated political, military, and civil society actors, to ensure cohesive decision-making and implementation. It provided technical guidance, harnessed data for strategic decisions and held implementers accountable. At its peak, the NCOC boasted nearly 300 personnel, including high-ranking military officers, a stark contrast to the limited staffing in most ministries. In addition, the response’s success is attributed to the perception of COVID-19 as an existential threat, leading to unprecedented collaboration and decisive actions that were enforced authoritatively. Conclusion Pakistan’s experience offers valuable insights for proactive management of health emergencies in resource-limited settings. It underscores the necessity for inter-sectoral dialog and data-driven policy implementation, especially in the context of political economies where activity-driven governance often overshadows objective-driven policy execution. However, the lessons from the COVID-19 response, including a blueprint for future epidemic responses and lessons for use of data and evidence in developing country health systems, if not institutionalized, risk being lost in the post-pandemic era.